Design of Application Administration outpatient at Dinas Kesehatan Tentara (DKT) Tuban - Chintyarani putri Ratnaningtyas; Haryanto Tanuwijaya; Achmad Arrosyidi (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Dinas Kesehatan Tentara (DKT) Tuban is a Army Health is hospital provide by the Indonesian Army that also serve to public people. There are many problems on DKT Tuban such as validation on medical record that happen effect by unintegrated medical record from registration until a month of patiens, patiens visit list, financial reports. Refers on that problem,this research offer design and build an outpatient administration application on DKT Tuban. This application discusses about patient registration, medical action, recording the disease, prescription drugs, payment, a month of patiens, patiens visit list, and financial reports that integration in one system. This application can be create some reports: reports outpatient, patiens visit list, financial reports, statical and graphical monthly reports, a mount of visit list each policlinic dayly. Keywords: medical record, administration, outpatient, policlinic, registration